Performance Analysis of Physical Education Teachers related to the Certification and Supervision Program in Tenggarong Seberang District - Saputra, Irawan Hadi; Rustiana, Eunike Raffy; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Teacher certification is one way for the government to improve the quality and professionalism of a teacher in improving the quality of education in Indonesia. Also, supervision can realize its function as a process of improving teacher quality through activities that emphasize self-realization, self-growth, and self-development. This study aims to analyze and describe the performance of physical education teachers who have certification and supervision in Tenggarong Seberang District. The approach used in this study is a case study method. Data collection techniques using interview techniques, observations and documents. The background of the study included certified physical education teachers in Tenggarong Seberang District. The source of the data is obtained from the headmaster, certified physical education teacher. The results of the study in five schools and six certified sports teachers and five school principals found no significant effect on the performance of physical education teachers. From the five schools, lack of discipline in teaching does not change very much in the learning method and age and disease factors that affect the performance of physical education teachers. This study recommends that to improve teacher performance, the government must regulate teacher policies regarding age and health as teacher support. Firmness as well as principals in arranging a teacher he leads.